IDENTITY CRISIS AND NATIONAL INTEGRATION: THE NIGERIA EXPERIENCE - UGWUIBE, Onyemaechi Christopher; ONAH, Francisca N (Social Science Research, 2021)
National integration has remained a gradual pursuit in many heterogeneous post-colonial states, Nigeria inclusive. The 1914 amalgamation exercise in Nigeria embarked upon by the British colonialists was a unification of more than 250 ethnic groups without unity. It was rather a marriage of convenience to ease administration and exploitation by the colonial powers. Thus, the fact of this colonial incursion could be said to mark the origin of identity crisis in Nigeria. Although various strategies and policies of national integration have been adopted in Nigeria to address the identity crisis since independence, the situation remains worrisome. It is against this back drop that this paper focuses on identity crisis and national integration in Nigeria. The study adopted the social identity theory in explaining identity crisis and national integration in Nigeria. Data for the study were gathered through secondary sources and analyzed using the content analytic method. The study reveals that the mechanism for national integration in Nigeria to some reasonable extents failed far below expectation. Among others, the paper recommends fairness and equity in appointments to political positions especially at the top echelon of government so as to reflect Nigeria’s federal character. Nigerians should also be acquainted with the ethics of patriosm.